Changing the contents of 137Cs in various objects of the forest ecosystems of the ChNPP exclusion zone during the calendar year - Zarubina, N.Ye. (Reports of the National Academy of Sciences of Ukraine, 2018)
Seasonal changes in the content of 137Cs in the soil and vegetation of forest ecosystems on the territory of the Chernobyl exclusion zone have been studied. Dependences of changes in 137Cs concentrations on the season of the year in the soils were not revealed. In the needles and branches of P. sylvestris, the maximum values of the 137Cs concentration are noted in spring and summer. As a result of the studies, a linear relation was found between seasonal changes in the 137Cs concentration in needles and branches of P. sylvestris in testing areas with different levels of contamination. Changes of the 137Cs content in the studied organs of P. sylvestris, which coincide in time on different testing areas, indicate common regularities of the 137Cs redistribution at the soilvegetation chain in forest ecosystems throughout the year.